2017
DOI: 10.1177/1358863x17724262
|View full text |Cite
|
Sign up to set email alerts
|

Internal mammary artery-to-pulmonary vasculature fistula: Systematic review of case reports

Abstract: The formation of a fistula between the internal mammary artery and the pulmonary vasculature (IMA-to-PV) is a rare anomaly. The etiology can be congenital; however, most recent cases have been associated with coronary artery bypass grafting, trauma, inflammatory conditions, chronic infections, or neoplasia. The knowledge base on the formation of these fistulas is derived primarily from case reports. To our knowledge, no systematic reviews or guidelines are available that provide information on how to manage th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Jabber et al described in a systematic review about internal thoracic artery to pulmonary vasculature fistula that the 59% of all fistula cases were found after CABG surgery. On the other hand, the case of secondary SAPVF following VATS like our case were just a few [ 2 ]. Traumatic change from dissection of the internal thoracic artery as a bypass graft may lead to internal thoracic artery to pulmonary vasculature fistula as Jabbar’s report [ 2 ].…”
Section: Case Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…Jabber et al described in a systematic review about internal thoracic artery to pulmonary vasculature fistula that the 59% of all fistula cases were found after CABG surgery. On the other hand, the case of secondary SAPVF following VATS like our case were just a few [ 2 ]. Traumatic change from dissection of the internal thoracic artery as a bypass graft may lead to internal thoracic artery to pulmonary vasculature fistula as Jabbar’s report [ 2 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…On the other hand, the case of secondary SAPVF following VATS like our case were just a few [ 2 ]. Traumatic change from dissection of the internal thoracic artery as a bypass graft may lead to internal thoracic artery to pulmonary vasculature fistula as Jabbar’s report [ 2 ]. Several other reports also described the secondary SAPVF usually developed as a consequence of inflammatory processes of the pleura or lung or after blunt, open chest trauma or thoracotomy [ 1 8 ].…”
Section: Case Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Admittedly, scientific robustness of the resulting data is far from the methodological rigor of a systematic review and meta-analysis of controlled clinical studies. However, several researchers [50][51][52] demonstrated that a methodological synthesis of case reports and case series could provide a useful addition to evidence-based medicine, particularly in the field of rare and heterogeneous conditions. Indeed, a systematic review of case reports or case series is the only available method for assessing the relationship between the PAES type and ABI score.…”
Section: Discussionmentioning
confidence: 99%